River Water Quality Based on Macrozoobentic Bioindicators in the Wonocolo Traditional Oil Mining Area - Laily Agustina Rahmawati; Norma Afiati; Thomas Triadi Putranto (Jurnal Ilmu Lingkungan)
Many studies declared traditional oil mining in Wonocolo caused pollution, including river pollution.  During Covid-19 Pandemic, traditional oil mining in Wonocolo has been interrupted because world oil prices decreased. This made selling price of crude oil in Wonocolo declined. This made traditional oil mining decreased because oil wells were temporarily closed. The decrease in traditional oil mining might affect river water quality in Wonocolo. In a prior  study, the researcher had investigated water quality of Bungsu and Kragsaan River in Wonocolo, based on physicochemical parameters. The river had improved quality during Covid-19 Pandemic, seen from the decrease in the content of several chemical pollutants. Through this study, the researcher examined macrozoobentos community structure as a bio indicator of water quality, like assessing water quality of Bungsu and Kragsaan River based on biological indicators. This study used observation method by determining sample points purposively. Sample of macrozoobentos was analyzed using biodiversity index of Shannon-Wiener, species evennes index, and dominance index. Results of study showed Bungsu River had low biodiversity (H’ index 0.000 – 1.040), distressed community at B-1 and B-3 but stable at B-2, like high dominance at B-1 and B-3 but low at B-2. Kragsaan River also had low biodiversity (H’ index 0.000 – 1.010), unstable community at K-1 and K-3 like distressed at K-2, and low dominance at K-2 and K-3 but medium at K-1. Based on H’ index, Bungsu River was in the heavily polluted category at B-1 and B-3 and the medium polluted category at B-2. Meanwhile, Kragsaan River was in the heavily polluted category at K-1 and K-2 and the medium polluted category at K-3. This means although decreased levels of chemical pollutants at the sampling locations meant an increase in quality of water body, river ecosystem had not been able to rejuvenate condition during Covid-19 Pandemic.